Pelatihan Menanam Tanaman Hias dengan Metode Tanam pada Polybag di Desa Alasdowo Kabupaten Pati - Marzuqotul Ilmiyah; Wahjoerini Wahjoerini (Jurnal Pengabdian KOLABORATIF, 2024)
Various types of planting media besides soil have different abilities in carrying out their functions as planting media to support the process of plant growth and development. In the world of agriculture and plantations, we often hear the term polybag as a planting medium, especially in nurseries and planting in polybags to save agricultural land. The choice of polybags as planting containers for cultivation is influenced by several factors, such as low price, rust resistance, durability, lightweight, uniform shape, does not get dirty quickly, and ease to obtain at agricultural supply stores or plastic shops. The purpose of this community service activity is to provide knowledge to the people in Alasdowo Village, Pati Regency regarding how to plant decorative plants using polybag media. The implementation method used is by providing information through discussions and questions and answers as well as direct practice on how to make planting media using polybags. The results obtained from this activity are increasing public knowledge about how to plant decorative plants using polybag media. The community can also take advantage of and use polybag media to fill in the empty land they have by planting decorative plants.